Orthodontic status and treatment need of 12-year-old children in South Africa : an epidemiological study using the dental aesthetic index - Van Wyk, Philippus J. (University of Pretoria, 2013)
Thesis (MChD (Orthodontics))--University of Pretoria, 2004.